Специфіка функціонування навчальних закладів професійного спрямування на Лівобережній Україні (друга половина ХІХ – початок ХХ ст.) - Сахній, Мирослава (Видавництво Львівської політехніки, 2012)
В статье проанализирована необходимость создания сети профессиональных школ в связи с отменой крепостного права и развитием экономики на Левобережной Украине во второй половине ХІХ – начала ХХ века. Описаны разные типы школ и раскрыта роль этих учебных заведений в системе образования того времени. The article analyses the necessity of creation the network of vocational schools in connection with serfdom abolishing and economics development on the Left-Bank Ukraine in the second half of the XIXth – in the beginning of the XXth centuries. The author describes different types of schools and shows the role of these educational establishments in the educational system of that time.
Специфика функционирования учебных заведений профессионального направления в Левобережной Украине (вторая половина ХІХ – начало ХХ в.)
Specific features of vocational educational establishments’ functioning on the Left-Bank Ukraine (the second half of the XIX – the beginning of the XX centuries)
Keywords: профессиональная школа; земства; содержание образования; квалифицированный специалист; ремесленные школы; учебно-воспитательный процесс; vocational school; counties; educational contexts; trained specialist; handicraft schools; educational process